Evaluation of online tutorial videos for classroom use in Home Economics - Panganiban, Ramon Paolo I. (College of Home Economics, University of the Philippines Diliman, 2018)
This qualitative study aimed to evaluate online tutorial videos OTVs for classroom use in home economics through three stages of action research which included identifying the points to consider in choosing cooking and sewing OTVs creating a tool for assessing cooking and sewing OTVs, and assessing the quality of selected cooking and sewing OTVs using the tool. Data were gathered through interview with selected experts and were analyzed using content analysis to create a rubric that was used to evaluate selected OTVs. Results show the important points to consider in choosing OTVs and these were categorized into two aspects, namely video content and video presentation. Under video content, the most important points to consider are: replicability of the demonstrated skill; suitability of the topic for online tutorial video, presentation of procedures, credibility of the presented information and demonstrated skill, and alignment of learning objectives. Under video presentation, the most important points to consider are: visual quality, camera angles and perspectives, audio quality, editing techniques, potential learner engagement, and demonstrator quality. These points were used as the criteria in the rubric that was created. The rubric made use of a grading system to determine if an OTV is a poor choice that is not suitable for learning; an average choice that is generally okay, but not suitable for classroom use; a good choice, but only as a supplement to a classroom demonstration; and an excellent choice that can be an alternative to a classroom demonstration. The rubric was used by the experts to reevaluate the same set of OTVs. The initial evaluation and reevaluation showed largely consistent assessments of whether the OTVs are suitable for classroom use or not. Improvements were made based from the comments and suggestions of the experts.